Effectiveness of Seventeen Brand Ambassadors in Mogu-Mogu Brand on Instagram Followers @mogumoguid - Feling Astuti Kusumaningsih; Ido Hadi; Astri Yogatama (Journal of Content and Engagement, 2025)
The purpose of this study was to determine how effective Seventeen's brand ambassador is in the Mogu-Mogu brand on Instagram followers @mogumoguid. This research is quantitative, using an online survey method and VisCAP theory (Visibility, Credibility, Attraction, Power). The number of respondents obtained and recorded was 100 respondents using a Likert scale. Respondents in this study are Instagram followers @mogumoguid who know or have seen Seventeen's content on Instagram @mogumoguid as a brand ambassador in the Mogu-Mogu brand. The results showed that all indicators were effective with an average result of 4.09, proving that Seventeen is an effective and appropriate brand ambassador for the Mogu-Mogu brand. The visibility indicator has the highest mean value of 4.23, which means that Seventeen's brand ambassadors are very popular on social media and can increase the attractiveness of the Mogu-Mogu brand.